Testing competing destinations gravity models – evidence from BRIC international - de Mello-Sampayo, F. (2017)
This paper derives and compares two competing-destinations formulation of the gravity model applied to trade in intermediates. We build a probabilistic input demand function from entropy maximization in which firms may purchase some of their inputs from other firms paying the required transport costs and accounting for the spatial structure of trading partners in a geographical system. In the second model, firms trade inputs to reduce the overall cost of production and intermediate sales are encouraged by low distance costs and low competition from alternative input sources. Even if the gravity equations look similar, we show that their underlying structures are different, and that the type of gravity equation has significant implications for the estimation technique adopted.